PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SMKN 1 MESUJI RAYA - Ardhi Wibowo; Dewi Yanti (UNISAN JURNAL, 2024)
This study aims to determine the principal academic supervision on the performance of Islamic religious education teachers at SMKN 1 Mesuji Raya and the factors that influence it. This type of research is field research with qualitative approach. From the research results revealed that, academic supervision carried out by the principal, namely: academic supervision related to learning planning consists of coaching in formulating learning objectives, academic supervision on the implementation of learning, including: giving examples in opening learning, giving examples in presenting learning materials , as well as academic supervision on the evaluation of learning, including: coaching in preparing the assessment of learning tools. While the factors that influence the implementation of academic supervision, namely: the supporting factor, namely the teacher who became the target of supervision of the principal to be cooperative and open to the supervision process conducted by the supervisor. Inhibiting factor of principal supervision in improving teacher performance, is the limited time allocation for the implementation of PAI learning in elementary school.